Comparison of Flow Boiling Pressure Drop Correlations for Smooth Macrotubes. Issue 6 (12th April 2016) - Turgut, Oğuz Emrah; Çoban, Mustafa Turhan; Asker, Mustafa
Abstract : This paper investigates two-phase pressure-drop correlations available in the literature and compares them with the experimental data in order to assess their performances in terms of prediction accuracy. Pressure drops for pure refrigerants and mixtures are predicted by comparing 1714 experimental data points with eight two-phase pressure drop correlations. In this context, R22, R407C, R410A, R744, R717, R404A, and R134a are selected as test refrigerants. A flow-pattern-based pressure-drop correlation developed by Moreno Quiben and Thome is also discussed. The Moreno Quiben and Thome model takes the effect of annular to dryout transition, and therefore maximum pressure drop occurs at the end of the annular flow regime. Results refer to experimental works in circular smooth tubes between 3.25 and 14.0 mm, for saturation temperatures between –30.0 and 50.0°C, mass fluxes between 100.0 and 1082.0 kg/m 2 -s, and heat fluxes from adiabatic to 36.8 kW/m 2 . The Muller-Steinhagen and Heck correlation shows better performance, predicting 61.7% of experimental data within a ±30.0% error band. It is also seen that the Chawla and Gronnerud correlations agree with experimental results only for R134a and R717.